Longitudinal follow up of serological response in children treated for Chagas disease - Moscatelli, Guillermo (2019)
BACKGROUND: Evaluation of therapeutic response in chronic Chagas disease is a major challenge, due to prolonged persistence of Trypanosoma cruzi-specific antibodies, lack of sensitivity of parasitological tests, and need for long-term follow-up to observe negative seroconversion of conventional serological tests (CS). The objective of this study was to evaluate F2/3-ELISA serology, a promising early biomarker of therapeutic response, and T.cruzi Polymerase chain reaction (PCR) for T. cruzi Deoxyribonucleic acid (DNA), for neonatal diagnosis and evaluation of parasitemia after treatment. METHODS: Prospective cohort study, with three-year clinical, serological and parasitological follow-up of pediatric Chagas disease patients treated with benznidazole. Serology was evaluated by Enzyme-Linked ImmunoSorbent Assay (ELISA), Indirect hemagglutination (IHA) and F2/3-ELISA; Parasitemia by microhematocrit (MH) and PCR. RESULTS: A cohort of 107 pediatric patients treated with benznidazole was enrolled in the study. ELISA and IHA were initially reactive in 100% of patients, F2/3-ELISA serology was reactive in 80% (86/107) and 91% (97/107) had detectable parasitemia. Seventy-six (71%) patients completed at least 36 months of serological follow up after treatment. Although a similar decreasing linear trend was observed for all serological tests, F2/3-ELISA presented earlier, age dependent, negative seroconversion compared to CS. All patients reaching undetectable CS titers had previously seroreverted by F2/3-ELISA. All patients with persistently decreasing antibody titers had negative PCRs throughout the follow up period. No new cardiological lesions were observed during the 3 years follow-up period. CONCLUSIONS: The data reported here, using CS, F2/3 ELISA and PCR provide support for the efficacy of benznidazole in congenital Chagas diseases. These results provide support for scaling up of screening, diagnosis and access to benznidazole treatment.